Transient Global Amnesia: A Case Report - Rison, Richard Alan (S. Karger AG, 2012)
INTRODUCTION: Transient global amnesia is a syndrome of temporary and reversible disruption of short-term memory accompanied by repetitive questioning. Although the etiology is unknown, the prognosis usually benign, and no particular treatment is required, it is important for all involved clinicians to recognize the diagnosis and possess knowledge about the evaluation of these affected patients. CASE PRESENTATION: A middle-aged Caucasian woman presented for neurologic evaluation for acute forgetfulness. Neurologic examination disclosed repetitive questioning with preserved orientation and no focal motor, speech, sensory, coordination, or cranial nerve deficits. Neurologic investigations did not reveal any pathologic findings. Her memory improved and reverted to normal baseline over the course of a 24-hour hospital stay. CONCLUSION: Transient global amnesia is an interesting syndrome of reversible anterograde amnesia associated with repetitive questioning that occurs with an unclear etiology in middle-aged and elderly individuals. Due clinical diligence is required in the investigation of these patients. Treatment is generally not required, and the condition usually does not recur. Clinicians, including neurologists, internists, family practice physicians, and psychiatrists, need awareness of this condition.